ASSESSMENT OF WIND CLIMATE RESOURCES ON THE TERRITORY OF THE REPUBLIC OF MOLDOVA FROM THE PERSPECTIVE OF CLIMATE CHANGE - BEJENARU, Gherman; DILAN, Vitalie (Studia Universitatis Babeș-Bolyai Geographia, 2025)
This paper investigates the changes in wind climate resources in the Republic of Moldova in the context of climate change. The study analyses wind speed and direction data from meteorological stations over the periods 1961-1990 and 1991-2020. Results show a decreasing trend in average wind speed, particularly in the southern and central parts of the country. Additionally, there is a slight shift in dominant wind directions. The study discusses the potential impact of these changes on wind energy utilization and emphasizes the need for updated wind resource assessments to support renewable energy planning.